Enhanced synthesis and stabilization of Mr 68,000 protein in transformed BALB/c-3T3 cells: candidate for restriction point control of cell growth. - Croy, R G (1983)
We have proposed that transformation of cells to tumorigenicity by chemical carcinogens can depend upon stabilization of a protein responsible for growth regulation. Cell kinetic experiments in which normal and benzo[a]pyrene-transformed BALB/c-3T3 cells were pulsed with cycloheximide indicated this protein should have a half-life of a few hours in normal cells and be considerably more stable in transformed cells [Campisi, J., Medrano, E. E., Morreo, G. & Pardee, A. B. (1982) Proc. Natl. Acad. Sci. USA 79, 436-440]. A protein with these properties has not yet been reported. We have searched for such a protein using two-dimensional electrophoresis to resolve protein from cells labeled with [35S]methionine. Among approximately 1,000 proteins that were resolved in these gels, we have found one that has a greater rate of synthesis and stability in benzo[a]pyrene-transformed than in untransformed cells. This result satisfies a necessary prediction of our labile protein hypothesis. We suggest that this protein could be important in determining the loss of growth regulation in these tumor cells.